ANALYSIS OF TEACHER'S POLITENESS INTERACTION WITH STUDENTS IN ENGLISH TEACHING - Sari, Winda; Daulay, Sholihatul Hamidah (Getsempena English Education Journal, 2023)
The goal of this study is to clarify various forms of speech politeness in the conversation of teachers and students working together to learn English in an elementary school in the city of Medan. Utilizing a qualitative approach, this investigation. Data collection methods include observational methods, transcription techniques, and various methods for taking notes. The aim is to determine the purpose of the principle of politeness in language selection learning exercises and how to speak politely between instructors and pupils. The findings of this study show that using courtesy in influences the language and the feelings of the teacher’s nine maxims from the ten maxims that teachers in linguistic etiquette, specifically: 1) Opinion Maxim Reticence, 2) Agreement Maxim3) Maxim of Sympathy, 4) Maxim of Generosity, 5) Maxim of Approval, 6) Maxim of Obligation S towards O, 7) Maxim of Wisdom 8) Maxim of Humility, 9) Maxim of Feeling Toughness. In conclusion, polite communication between teachers and Students frequently speak Indonesian instead of English. Here is the teacher's attention in teaching in class with polite language.